Climatic controls and climatic proxy potential from glacier retreat on Lewis Glacier, Mt Kenya - Prinz, Rainer (2015)
The Lewis Glacier on Mt Kenya (0.1 km², 0°9'S, 37°18'E) has a unique history of detailed study, making it among the best documented tropical glaciers. Since a maximum extent in the late 19th century (L19) Lewis Glacier has been experiencing considerable retreat, which has been reported in a series of maps throughout the 20th and 21st century. In 2010 the most recent survey of its surface topography and ice thickness was performed. Total ice volume in 2010 was 1.90 +- 0.30 x 10hoch6 m³ with a mean (maximum) ice depth of 18 +- 3 m (45 +- 3 m), which is one order of magnitude larger than previously published values. In 2010, the glacier had lost 90% (79%) of its 1934 glacier volume (area), with the highest rates of ice volume loss occurring around the turn of the century. An automated weather station at the glacier surface provides 2.5 years of meteorological data in hourly resolution to study energy and mass exchanges between the glacier surface and the atmospheric layer above. Using a physical mass and energy balance model, the surface energy fluxes were calculated at the point of meteorological observation, resulting in high melt rates throughout the year and sublimation rates lower than reported for other tropical glaciers. Short-wave radiation provides the greatest net source of energy to the glacier surface and long-wave net radiation is the largest energy sink. Cloud cover typically reduces the net radiation balance compared to clear sky conditions, and thus the frequent formation of convective clouds over the summit of Mt Kenya, and the associated higher rate of snow accumulation are important in limiting the rate of mass loss from the glacier surface. Glacier-wide mass and energy balance modelling with synthetic climate scenarios, which were sampled from the meteorological measurements and account for coupled climatic variable perturbations, reveal that the current mass balance is most sensitive to changes in atmospheric moisture (via its impact on solid precipitation, cloudiness and surface albedo). ...